PENGGUNAAN SUZUKI INTERACTIVE BROCHURE (SIB) SEBAGAI PLATFORM PENDUKUNG PENJUALAN MOBIL BAGI SALESMAN - Samuel Banurea (KINDAI, 2017)
Abstract : The development of Information and Communication Technology in Indonesia is very rapid and it’s seen by PT. Suzuki Indomobil Sales for creating mobile apps that serve as a car sales supporting platform for Salesman. During this time, Salesman using tools, namely brochures to explain the product specification information to consumers. It’s seen not too effective and efficient because of the limited of brochures that the supply to dealer or the limitations of the production cost of printing brochures at the dealers. With this mobile apps, called Suzuki Interactive Brochure (SIB), Salesman can download this app in their gadget and use it in their daily work. By using the Suzuki Interactive Brochure (SIB) application, Salesman can select the detail product specification, simulation color of the product, the comparison with others Suzuki Products, as well as information about the network of outlets Suzuki 3S (Sales, Service & Spare part) and 1S (Sales) connected with contact dealers and outlets throughout Indonesia. This mobile apps makes salesman and consumers easier, and can save production cost for brochure printing, thus lowering operating costs at the dealership. Keywords : Suzuki Interactive Brochure, salesman, mobile apps Abstrak : Perkembangan Teknologi Komunikasi dan Informasi di Indonesia sangat pesat dan hal ini dilihat oleh PT. Suzuki Indomobil Sales untuk menciptakan mobile apps yang berfungsi sebagai platform pendukung penjualan mobil bagi Salesman. Selama ini Salesman menggunakan tools, yaitu brosur untuk menjelaskan informasi spesifikasi produk kepada konsumen. Hal ini dilihat kurang efektif dan efisien karena keterbatasan jumlah brosur yang di supply ke dealer maupun keterbatasan biaya produksi cetak brosur di dealer. Dengan aplikasi Suzuki Interactive Brochure (SIB), Salesman dapat memilih menu detail spesifikasi produk, simulasi warna produk, komparasi dengan produk Suzuki lainnya, serta informasi mengenai jaringan outlet Suzuki 3S (Sales, Service & Sparepart) dan 1S (Sales) yang terhubung dengan contact dealer maupun outlet di seluruh Indonesia. Mobile apps ini memberi kemudahan bagi Salesman dan konsumen, serta dapat menghemat biaya produksi cetak brosur, sehingga menurunkan biaya operasional di dealer. Kata Kunci : Suzuki Interactive Brochure, salesman, mobile apps